2021
DOI: 10.1186/s12889-020-09999-2
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression symptoms in survey-based research: a structural equation analysis

Abstract: Background Since the last decade, postpartum depression (PPD) has been recognized as a significant public health problem, and several factors have been linked to PPD. Mothers at risk are rarely undetected and underdiagnosed. Our study aims to determine the factors leading to symptoms of depression using Structural Equation Modeling (SEM) analysis. In this research, we introduced a new framework for postpartum depression modeling for women. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Postpartum depression (PPD) is defined as a non-psychotic depressive episode beginning in or extending to the postpartum period [ 1 ]. In addition to the similar symptoms of depression at other times of life such as loss of interest, insomnia, irritability, exhaustion, poor concentration, low self-respect, and thoughts of suicide, women who have PPD also experience guilty feelings about taking care of their new baby [ 2 , 3 , 4 , 5 ]. Due to the high incidence worldwide, PPD has been recognized as a severe public health problem during the last decades [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Postpartum depression (PPD) is defined as a non-psychotic depressive episode beginning in or extending to the postpartum period [ 1 ]. In addition to the similar symptoms of depression at other times of life such as loss of interest, insomnia, irritability, exhaustion, poor concentration, low self-respect, and thoughts of suicide, women who have PPD also experience guilty feelings about taking care of their new baby [ 2 , 3 , 4 , 5 ]. Due to the high incidence worldwide, PPD has been recognized as a severe public health problem during the last decades [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the similar symptoms of depression at other times of life such as loss of interest, insomnia, irritability, exhaustion, poor concentration, low self-respect, and thoughts of suicide, women who have PPD also experience guilty feelings about taking care of their new baby [ 2 , 3 , 4 , 5 ]. Due to the high incidence worldwide, PPD has been recognized as a severe public health problem during the last decades [ 3 , 6 ]. Longitudinal and epidemiological studies have found the at the prevalence of PPD in different countries varied from 10% to more than 25% in the first year postpartum [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations